Rancang Bangun PLTMH Menggunakan Turbin Cross-Flow berkapasitas 1 Kw untuk Daerah Terpencil dengan Sumber Air yang Terbatas - Joko Pratilastiarso; Mohamad Hamka (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Electricity crisis that occurred encourages the implementation of renewable energy in a way to occupy the electricity supply needs. Implementation of the MHP(Micro Hydro Powerplant) is the best alternative to escape the electricity crisis. Given the potential of hydropower spread almost throughout Indonesia, the power is estimated at 75000 MW, 500 MW which is the potential for micro hydro power plant (MHP). Unfortunately, the potential of micro hydro is only 500 MW, is used only 4% of its course is 20 MW. Another problem is how to build a micro-hydro power plants in areas with limited water supply source. At this research project a micro hydro power plant has designed using cross-flow turbines that can be installed acording to the conditions above, as the efforts of using renewable energy to occupy the electricity supply needs. The design of the turbine is later evaluated to obtain optimal value of the calculation. Cross-flow turbines are designed at 13 m and the discharge head is 0.03 m3 / s. According to the design the maximum speed is 412.63 rpm, the maximum speed is expected to be produced not far adrift from the design. Maximum power turbine which is expected to reach the amount of 1 kW with an efficiency of 80%.